Bending Behaviour Of Cold Formed Steel Structural Member With Perforated Section In House Framing System - Lim, Yon Sheng (Universiti Sains Malaysia, 2017)
Due to highly demand of housing, the usage of cold formed steel section as framing system was introduced. C-channel cold-formed steel is widely used in construction industry due to its light weight, cost-effectiveness, and high strength-to-weight ratio. In order to reduce the weight of steel beams, accommodate plumbing and electrical facilities., web profile with openings has been introduced in the construction industry. In this study, bending behavior of cold-formed steel framing system and effective cost reduction between perforated and non-perforated steel section in steel framing system are investigated. The results are expressed in terms of displacement and yield moment. Using Staad.Pro and Lusas, a total of 26 set of nonlinear analyses were carried out to investigate the effects of opening spacing, edge distance and thickness of section on bending behavior. The result showed that increasing the opening spacing and edge distance would increase the bending capacity. C-channel steel section showed better moment resistance in thicker section. The result was then compared with the C-channel steel section without opening. From the analysis, it was observed that C-channel steel section without opening had higher bending capacity than C-channel steel section with opening in major axis. However, there is 0% of difference in terms of yield moment when comparing C-channel section with 0.4D of square opening and 0.3L edge opening as well as 0.1L opening space with C-channel section without opening while reducing the volumes up to 7.28%. Thus, C-channel section with 0.4D of square opening, 0.3L edge opening and 0.1L opening space give a very effective cost reduction.